(untitled) (Research, Society and Development, 2021)
This study investigated the relationship between dietary patterns and lipid profile in adolescents. This is a cross-sectional study involving a probabilistic sample of 1,188 students aged 11 to 18 years, from public schools in the city of Salvador-Bahia. Food consumption was analyzed using a semi-quantitative food frequency questionnaire and dietary patterns were identified using factor analysis using the principal component technique and scores categorized into tertiles. Associations between dietary pattern and lipid profile (total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides) were performed by polytomous logistic regression adjusted for sex, age, and nutritional status. Three dietary patterns were identified, characterized as: unhealthy, healthy and traditional. In the adjusted models, a significant association was found between food consumption in the lowest tertile of the healthy pattern, with high concentration of triglycerides (odds ratio =1.88; 95% confidence interval =1.10-3.22) and low cholesterol levels high-density lipoprotein (odds ratio: 1.62; 95% confidence interval = 1.01-2.62), when compared to consumption in the highest tertile of this pattern. An association was identified between lower adherence to the healthy pattern with low serum levels of high-density lipoprotein and high triglycerides. There was no association between unhealthy and traditional patterns and lipid profile.